Passive ocean bottom geophone and hydrophone data from the German Entenschnabel area acquired during cruise MSM100 between 13.5.2021 - 15.5.2021 - Florian Schmid (PANGAEA, 2025)
The dataset contains 2.5 days of passive recording from a network of 12 ocean bottom geophone stations (with hydrophones) deployed in the German EEZ of the North Sea. The seismic sensors instruments used for acquisition include 4.5 Hz geophones and HTI-PCA-04 ULF Hydrophones. Originally, the instruments were deployed during a 3D seismic experiment, which is described in the related and referenced cruise report for Maria S. Merian expedition MSM100. The data uploaded here contain an time-interval where no active seismic shooting was performed. Thus, they represent passive seismic data. The raw data are provided as mini-seed formatted files. They can be viewed, edited and analysed with various seismic and seismology related software tools. Further details about the deployment may be retrieved from the related MSM100 cruise report.